2022
DOI: 10.3389/fphar.2022.893635
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Pharmacodynamics and Antiviral Efficacy of the MEK Inhibitor Zapnometinib in Animal Models and in Humans

Abstract: The mitogen-activated protein kinase (MEK) inhibitor zapnometinib is in development to treat acute viral infections like COVID-19 and influenza. While the antiviral efficacy of zapnometinib is well documented, further data on target engagement/pharmacodynamics (PD) and pharmacokinetics (PK) are needed. Here, we report zapnometinib PK and PD parameters in mice, hamsters, dogs, and healthy human volunteers. Mice received 25 mg/kg/day zapnometinib (12.5 mg/kg p. o. twice daily, 8 h interval). Syrian hamsters rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 58 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…Many of the hydroxylated metabolites were subsequently glucuronidated leading to a fast excretion in the feces (Wabnitz et al, 2004). Since glucuronidation was not observed to such an extend with zapnometinib in rats, this could be a reason for a prolonged presence of zapnometinib in animals and humans compared to CI-1040 (Lorusso et al, 2005;Koch-Heier et al, 2022). In summary, the metabolic profile confirms the good stability and bioavailability with normal metabolization of the compound for elimination of the drug from the body, demonstrating an important role for metabolizing enzymes for the ADME profile of zapnometinib, Determined by oxidation and liquid scintillation analysis (LLOQ = 0.011-0.031 µg equiv zapnometinib/g).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many of the hydroxylated metabolites were subsequently glucuronidated leading to a fast excretion in the feces (Wabnitz et al, 2004). Since glucuronidation was not observed to such an extend with zapnometinib in rats, this could be a reason for a prolonged presence of zapnometinib in animals and humans compared to CI-1040 (Lorusso et al, 2005;Koch-Heier et al, 2022). In summary, the metabolic profile confirms the good stability and bioavailability with normal metabolization of the compound for elimination of the drug from the body, demonstrating an important role for metabolizing enzymes for the ADME profile of zapnometinib, Determined by oxidation and liquid scintillation analysis (LLOQ = 0.011-0.031 µg equiv zapnometinib/g).…”
Section: Discussionmentioning
confidence: 99%
“…Zapnometinib is an orally available MEK-inhibitor with a dual therapeutic effect that is currently under development for the treatment of severe viral diseases like COVID-19 and influenza. Preclinical in vitro and in vivo studies demonstrated efficacy and safety of the drug ( Laure et al, 2020 ; Schreiber et al, 2022 ; Koch-Heier et al, 2022 ), which allowed further investigations in Phase 1 (NCT04385420) and Phase 2 (NCT04776044) clinical trials in humans. Zapnometinib is the active metabolite of CI-1040, a drug that was developed to treat cancer ( LoRusso et al, 2005 , Rinehart et al, 2004 ; Barrett et al, 2008 ; Seibold-Leopold et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ras activates Raf, which then phosphorylates MEK1 and MEK2. Activated MEK1/2 subsequently activates ERK1 and ERK2 through phosphorylation ( Sebolt-Leopold et al, 1999 ; Planz, 2013 ; Koch-Heier et al, 2022 ). ERK1/2 constitutes the only known substrate of MEK1/2 ( Lorusso et al, 2005 ; Yoon and Seger, 2006 ; Koch-Heier et al, 2022 ) and eventually influences proliferation, differentiation, apoptosis and survival ( Sebolt-Leopold, 2004 ; Lorusso et al, 2005 ; Meier et al, 2005 ; Yoon & Seger, 2006 ), but also cytokine production and cellular immune responses ( Ludwig et al, 2003 ; Planz, 2013 ; Koch-Heier et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%